To Cut or Not to Cut? : That is the (Central Bank's) Question In Search of the Neutral Interest Rate in Latin America - Magud, Nicolas; Tsounta, Evridiki (Washington, D.C. : International Monetary Fund, 2012)
This paper estimates neutral real interest rate (NRIR) ranges for 10 Latin American countries that either have full-fledged inflation targeting regimes in place or have recently adopted them, using an array of methodologies commonly used in the literature. We find that NRIRs have declined in the last decade, with more economically and financially developed economies exhibiting lower NRIR levels. Based on the estimated NRIRs, we assess that the current monetary stance (measured by the interest rate gap) is appropriately neutral in most of the considered economies, in line with closing output gaps. We also observe that the interest rate gap can be a good predictor of future inflation dynamics and economic growth. In addition, looking at the recent experiences in Brazil and Peru, we suggest that macro-prudential policies could affect the monetary stance even in the absence of direct interest rate changes, through affecting the NRIR.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet